DAYA TERIMA DAN KARAKTERISTIK MINUMAN SERBUK ‘TERAI’ BERBAHAN DASAR TEMULAWAK (Curcuma xanthorriza Roxb) DAN SERAI (Cymbopogon Citratus) - Yola Mastika Sari; Ayu Pravita Sari; Miratul Haya (Universitas Bengkulu, 2021)
Background : Powder drink is a powder or granule product that made from a mixture of sugar and spices with or without the addition of other ingredients. Raw ingredients of powder drink can make from various kinds of plants, such as turmeric and lemongrass, that are both of ingredients contain active compounds that can function to maintain body immunity, especially during a pandemic like now. The criterias of a good powder drink are taste, smell, color and appearance that are comparable to fresh products, have nutritional characteristics and have a good storage stability.Purpose : This study aims to determine the organoleptic acceptability of the